Human like me: Evidence that I‐sharing humanizes the otherwise dehumanized. (17th July 2017) - Pinel, Elizabeth C.; Yawger, Geneva C.; Long, Anson E.; Rampy, Nolan; Brenna, Robert; Finnell, Sasha K.
Abstract : People persistently undermine the humanness of outgroup members, leaving researchers perplexed as to how to address this problem of 'dehumanization' (Haslam & Loughnan, 2014, Ann Rev of Psychol, 65, 399 ; Leyens, 2009, Group Process Intergroup Relat, 12, 807). Here, we test whether I‐sharing (i.e., sharing a subjective experience) counters this tendency by promoting the humanization of outgroup members. In Study 1, White participants had a face‐to‐face meeting with a White or Black confederate and either did or did not I‐share with this confederate. The extent to which participants humanized the outgroup member depended on whether or not they I‐shared with her. Study 2 tested the effect of I‐sharing on the two distinct dimensions of dehumanization (Haslam, 2006, Pers Soc Psychol Rev, 10, 252). Conceptually replicating the results of Study 1, participants who I‐shared with a social class ingroup or outgroup member rated their partner as higher in human nature than those who did not I‐share with their partner. These results add to the growing literature on I‐sharing's implications for intergroup processes and suggest effective ways of tackling a persistent problem.